2018
DOI: 10.1016/j.gaitpost.2017.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Virtual reality balance training for elderly: Similar skiing games elicit different challenges in balance training

Abstract: Our results show the importance of assessing the movement challenge in games used for balance training. Similar games impose different challenges, with the control sensors and their gain settings playing an important role. Furthermore, adaptations led to a decrease in challenge in Wiiski, which might limit the effectiveness of the game as a balance-training tool.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 27 publications
2
36
1
2
Order By: Relevance
“…The remaining two were off-the-shelf games: Adventure, Kinect Adventures (Ubisoft, Rennes, France) and Kinski, Kinect sports season 2 (Microsoft Studios, Redmond, WA, US). Adventure and Kinski were included in this study because they showed to be the games that previously had most induced muscle activity and weight shifts [22,24].…”
Section: Gamesmentioning
confidence: 99%
See 3 more Smart Citations
“…The remaining two were off-the-shelf games: Adventure, Kinect Adventures (Ubisoft, Rennes, France) and Kinski, Kinect sports season 2 (Microsoft Studios, Redmond, WA, US). Adventure and Kinski were included in this study because they showed to be the games that previously had most induced muscle activity and weight shifts [22,24].…”
Section: Gamesmentioning
confidence: 99%
“…Based on the recommendations for balance and strength training, obtained from the literature [2,6,18,27] and our previous work in training using exergames [22,24,25], several concepts to be addressed in exergames balance training applications were proposed. In Fig.…”
Section: Gamesmentioning
confidence: 99%
See 2 more Smart Citations
“…Rehabilitation using VR appeals to elderly patients because it gives them the possibility to diversify treatment by introducing alternative forms of activity. However, there is still a demand for more randomized clinical studies that would confirm the efficacy of this form of activity, especially in patients suffering from the frailty syndrome, who are the largest group of beneficiaries of this type of rehabilitation [27,28].…”
Section: Virtual Reality In Rehabilitationmentioning
confidence: 99%